Analisis Sistem Instalasi Listrik Pada Menara Transmisi Telekomunikasi di Kota Makassar - Ashari, Hilda; Dessy Ana Sari (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2024)
This research is a quantitative study using survey methods aimed at determining the viability of electrical installations on telecommunications transmission towers. The research was conducted at UPD007 Telkomas, Makassar City, South Sulawesi Province. The variables in this study are the security of electrical installations, transmitters of electric installations and grounding of electricity installations. Data collection techniques are observation, documentation, interview and measurement techniques. Data analysis techniques used are descriptive data analysis using Persyaratan Umum Instalasi Listrik (PUIL) 2011. The results of the research show that the use of the security of the electrical installation at each point is said to be appropriate based on its type and capacity. The transmitter of the electrical installation used in its entirety is said to be valid based on the peripheral area, whereas the color of the transmitter indicates only the entire neutral transmitter, grounded transmitter and DC transmitter conforming to the standard using Persyaratan Umum Instalasi Listrik (PUIL) 2011. The grounding resistance obtained on each protection is fully said to be eligible under the provisions of Persyaratan Umum Instalasi Listrik (PUIL) 2011.